Molecular and Biochemical Evidence of Edaravone's Impact on Dasatinib-induced AGS Cell Senescence: A Promising Strategy for Gastric Cancer Therapy - Rahimifard, Mahban; Baeeri, Maryam; Manavi, Mohammad Amin; Khalid, Madiha; Foroumadi, Roham; Haghi-Aminjan, Hamed; Abdollahi, Mohammad (Current Medicinal Chemistry, 2026)
IntroductionInternal or external stress can induce cellular senescence, which reduces cell division. These metabolically active cells contribute to medication resistance. We examined the potential for edaravone (Eda) to cause apoptosis in dasatinib (Das)-induced senescent gastric adenocarcinoma cells (AGS). Our goal was to develop a new stomach cancer treatment.MethodsAll Eda doses evaluated were nontoxic to cells. Das decreased AGS cell survival in a dose-dependent manner. The study found that Das (5-10 μM) and Eda (100 μM) caused cell senescence in AGS cells. This was shown by increased β-galactosidase enzyme activity and reactive oxygen species levels and decreased telomerase enzyme activity. These are the biggest signs of aging.ResultsThis combination therapy also upregulated the expression of cell-senescence genes p53, p16, p21, and p38. This resulted in increased expression of inflammation genes such as TNF-α, IL-1β, and IL-6.ConclusionThe scratch assay showed that this combination medication down-regulated the cell migration-regulating matrix metalloproteinase-2 (MMP2) gene. Both Das and Eda decreased AGS cell proliferation, suggesting treatment with Eda may prevent metastasis.
Keywords: chemotherapy